Corporate Financing and Risk Management in the Banking Sector in Uganda During and Post Covid-19. Evidence from Kabale District - Semusu, Alex; Byamukama , Eliab Mpora (International Journal of Finance and Accounting, 2024)
The study examined the effects of corporate financing and risk management in the banking sector in East Africa during and Post Covid-19 tapping on evidence from the Kabale district in Uganda. It was guided by specific objectives, the effect of Bonds on risk management in the banking sector during and post COVID-19, the effect of treasury bills on risk management in the banking sector during and post COVID-19, and the effect of debt management on risk management in the banking sector during and post COVID-19. A descriptive research design was adopted in this research. Both primary and secondary data were used in this study. The population of the study was 97 technical staff. Purposive and random sampling techniques were applied in the study. Data was collected from 78 staff of selected commercial banks in the Kabale district using a structured questionnaire. Both correlation and regression analysis were used. The study revealed that the board of directors set strategies on bond issuance and were effectively communicated within the bank in the form of policies and procedures by the top management (M =4.2, SD = 0.34). The findings showed that the bank has set in place principles of short-term crediting (M = 4.6, SD = 0.32). The bank undertakes regular monitoring of the total value of gross daily payments made and received (M = 4.8, SD = 0.18). Involves identification of existing sources of treasury bills as well as treasury bills that may arise from new business products or activities (M = 4.7, SD = 0.30). The average lessons undertaken was (M = 4.3, SD = 0.13). Debt management was also implemented by the banking sector. It was reported that the debt management efforts of the bank were supported by senior Management (M = 4.2, SD = 0.42). It was also revealed that the management efforts of the institution were well communicated to them (M = 4.2, SD = 0.18). There is a need to set up strong structures for the management of corporate financing in order to enhance risk management in the banking sector.